The resurgence of income inequality in Asia-Pacific: the role of trade openness, educational attainment and institutional quality - Sharon, G. M. Koh; Grace, H. Y. Lee; Audrey, K. L. Siah (Penerbit Universiti Kebangsaan Malaysia, 2022)
Within-country inequality is on the rise in many Asian countries despite rapid educational expansion, poverty reduction and export-driven macroeconomic growth. This trend raises questions about the role and effectiveness of governments in redistributing income and wealth. Therefore, our study re-examines the effects of trade openness and educational attainment on income inequality while additionally investigating the role of governance on several dimensions. The study is conducted on nineteen Asian economies for the period 1990-2019. Methodologically, we follow Generalised Methods of Moments using dynamic panel procedures to improve previous efforts to examine the trade-inequality relationship. We hypothesize that good institutions can generate better distributional outcomes in terms of foreign trade and educational attainment. To test this, aggregate measures of institutions on five dimensions of governance - government stability, corruption, law and order, democratic accountability, and bureaucratic quality are incorporated into the empirical model. Our empirical results reveal that controlling for the country’s income level, increasing trade openness and overall improvements in institutional quality contribute to reducing income inequality in the Asia-Pacific region. However, educational attainment has an inequality-widening effect during our period of study. We conclude by discussing other possible explanations for rising inequality in the region, and in that context, the role of public policy in ensuring equitable distributions.